Optimalisasi Tata Letak Watchroom Guna Meningkatkan Pelayanan Operasional di Unit PKP-PK Bandar Udara Internasional Kualanamu - Elisabet Putri Br. Sihaloho; Martha Saulina; Rahmawati Sukra (LPPM Politeknik Pratama, 2026)
This study explores efforts to optimize the layout of the watchroom at the PKP-PK Unit at Kualanamu International Airport with the aim of improving the effectiveness of operational services and response to emergencies. A descriptive qualitative method was chosen, involving field observations and in-depth interviews with personnel, to map existing conditions and identify challenges faced. The findings revealed that limited visibility and the watchroom's non-strategic location hindered comprehensive monitoring of airside activities, thereby slowing decision-making in critical situations. The recommendations provided include reorganizing the space with a focus on 360-degree visibility, ergonomic work access, and compliance with international regulatory standards (ICAO and PR 30 of 2022). The implementation of a more optimal room design is expected to enhance communication speed, monitoring effectiveness, and personnel readiness in handling incidents, thereby significantly strengthening the quality of PKP-PK services and operational safety at the airport.